Characterization of anodic oxide film growth on Ti6Al4V in NaTESi electrolyte with associated adhesive bonding behaviour. (10th November 2015) - Liu, Z.J.; Zhong, X.; Liu, H.; Tsai, I.-L.; Donatus, U.; Thompson, G.E.
Abstract: The formation of anodic oxide films on the Ti6Al4V alloy in the NaTESi electrolyte has been studied in the present paper. An anodic film with a shallow pore-like texture was formed after anodizing to 10 V. Porous anodic films with increased porosity were generated after anodizing from 20 to 40 V, and the pores were developed mainly within the α phase. Significant amounts of sodium species were incorporated in the films, and the amount increased with increasing anodizing voltage. The current efficiency for the anodic film growth increased from 10 to 30 V, but decreased from 30 to 40 V due to the occurrence of more oxygen evolution. The film thicknesses determined by RBS were 15 nm, 65 nm, 115 nm and 250 nm at 10, 20, 30 and 40 V respectively. The film thickness generated at 10 V showed good agreement with the thickness of 11 nm revealed by transmission electron microscopy. The Raman spectra indicated that the degree of crystallinity of the anodic film increased at higher voltages. The dielectric permittivity of the film was estimated as ∼118 according to the results from transmission electron microscopy and electrochemical impedance spectroscopy. Single-lap shear bonding tests were employed to compare the strength of adhesively joined titanium alloy anodized to different voltages. The results revealed appreciable increase in bond strength with increasing anodic film thickness.